Pendekatan Balanced Scorecard dalam Mengukur Kinerja Baitul Mal wa Tamwil Amanah Kota Banjarmasin - Difi Dahliana (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2022)
Performance measurement that only focuses on the financial health aspect as applied by most BMT, does not provide comprehensive results. Contemporary performance measurement known as the Balanced Scorecard (BSC) is more comprehensive because it does not only focus on aspects of financial health but also non-financial aspects. This study aims to measure and evaluate the performance of BMT Amanah with approach BSC consisting of financial, customer, perspectives internal business processes, as well as growth and learning. After processing and quantitative descriptive analysis, the results show that: 1) the performance of the financial perspective has a score of 2.3, which means that it is not good; 2) the performance of the customer perspective has a score of 3.4 which means it is quite good; 3) the performance of the internal business process perspective has a score of 2.2 which means it is not good; 4) the performance of the growth and learning perspective has a score of 3.1 which means it is quite good. Thus, BMT Amanah's strategic objectives, which are too people-centric, resulting in the neglect of the business process and financial perspectives, must be evaluated. Pengukuran kinerja yang hanya fokus pada aspek kesehatan keuangan seperti yang diterapkan oleh kebanyakan BMT, tidak memberikan hasil yang komprehensif. Pengukuran kinerja kontemporer yang dikenal dengan Balanced Scorecard (BSC) lebih komprehensif karena menekankan keseimbangan dan keterkaitan antar aspek keuangan dan non keuangan. Penelitian ini bertujuan untuk mengukur dan mengevaluasi kinerja BMT Amanah dengan pendekatan BSC yang terdiri dari perspektif keuangan, pelanggan, proses bisnis internal, serta pertumbuhan dan pembelajaran. Setelah dilakukan pengolahan dan analisis deskriptif kuantitatif, hasilnya menunjukkan bahwa: 1) kinerja perspektif keuangan skornya 2,3 artinya kurang baik; 2) kinerja perspektif pelanggan skornya 3,4 artinya cukup baik; 3) kinerja perspektif proses bisnis internal skornya 2,2 artinya kurang baik; 4) kinerja perspektif pertumbuhan dan pembelajaran skornya 3,1 artinya cukup baik. Dengan demikian, sasaran strategik BMT Amanah yang terlalu people-centric sehingga mengakibatkan perspektif proses bisnis dan perspektif keuangan menjadi terabaikan, harus dievaluasi.